(untitled) - Sting; (Musician); composer; Hartley, David; 1952-; Goodman, John (Burbank, CA, 2005)
After Emperor Kuzco is turned into a llama by his devious advisor, he turns to shepherd Pacha to help him regain his former life as ruler.
Keywords: Drama; Drama; Llamas; Kings, queens, rulers, etc; Llamas; Juvenile films; Emperors; Juvenile films; Films for the hearing impaired; Video recordings for the hearing impaired; DVD-Video discs; Childrens films; Animated films; Comedy films; Feature films